Development and Evaluation of Nano-based Ocular Drug Delivery System for Glaucoma - Andanayya Saraganachari; Dr. Vishal Kumar Gupta (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Brinzolamide (BZ) is an intraocular pressure-reducing agent with low solubility. The purpose of the present study was designed to increase the Brinzolamide bioavailability by Nano micellar formulation (NMs) as an ocular drug delivery system to increase the therapeutic efficacy. Brinzolamide Nano micellar were prepared by the solvent evaporation method by using a Rota evaporator. Based on initial release studies, different formulations were prepared in various ratios of Soya phosphatidylcholine, Polysorbate 80, and Sodium glycocholate. The prepared preparation was characterized by further physicochemical investigations such as drop size, Assay, pH, osmolality, Zeta potential, and viscosity. Brinzolamide micellar formulation (Trial-5) with suitable physicochemical properties exhibited high formulation stability under different conditions. These formulations included those with a low Drop Size of 28.8 µl, Osmolality 311 mOsmol/kg, Zeta potential -0.837 mV, pH 7.2 Drug content estimation (Assay) 101.9%, and stability for at least 6 months at 25 °C/40% RH and 40 °C/25% RH. The Brinzolamide ophthalmic without preservative solution was packed in a preservative-free container by using the Novelia packing system which enhanced the stability of the preparation throughout the in-use shelf life of the solution. Finally, it was concluded that Brinzolamide NMs without preservatives packed in the Novelia packing system will be an effective package model for the Brinzolamide ophthalmic solution.